Corrigendum to "Tutorial on Applied Study Designs in Medical Research" [JCHR 2022; 11(3): 202-209] - sajjad Bahariniya; Farzan Madadizadeh; Elham Khaledi; Farnoosh Qomi (Shahid Sadoughi University of Medical Sciences, 2022)
The mistake made in article 9 is that the name of the fourth author is "Mehrnoosh Qomi", while the correct name is "Farnoosh Qomi".On behalf of the author, the publisher wishes to apologize for this error. The online version of article has been updated on 28 September 2022 and can be found at https://jhr.ssu.ac.ir/article-1-892-en.html.